Development and validation of a simple, rapid and stability-indicating high performance liquid chromatography method for quantification of norfloxacin in a pharmaceutical product - Chierentin, Lucas; Salgado, Hérida Regina Nunes [UNESP] (OMICS International, 2013)
A stability-indication high performance liquid chromatographic method has been developed for the determination of norfloxacin in tablet dosage forms. Optimum separation was achieved in less than 7 minutes using Eclipse Plus Zorbax C18 Agilent, 150 mm×4.6 mm i.d., 5 μm particle size column. The analyte was resolved by using a mobile phase 5% acetic acid aqueous solution and methanol (80:20, v/v) at a flow rate 1.0 ml/min on an isocratic high performance liquid chromatographic system at a wavelength of 277 nm. Linearity, system suitability, precision, sensitivity, selectivity, specific, and robustness were established by International Conference Harmonization guidelines. For stress studies the drug was subjected to photolysis, oxidation, acid, alkaline and neutral conditions. The analytical conditions and the solvent developed provided good resolution within a short analysis time and economic advantages. The proposed method not required sophisticated and expensive instrumentation.
Keywords: Degradation products; HPLC-UV; Liquid; Chromatography; Norfloxacin; Stability-indicating method; Validation